2010
DOI: 10.1002/jbmr.270
|View full text |Cite
|
Sign up to set email alerts
|

In vivo discrimination of hip fracture with quantitative computed tomography: Results from the prospective European Femur Fracture Study (EFFECT)

Abstract: In assessing osteoporotic fractures of the proximal femur, the main objective of this in vivo case-control study was to evaluate the performance of quantitative computed tomography (QCT) and a dedicated 3D image analysis tool [Medical Image Analysis Framework-Femur option (MIAF-Femur)] in differentiating hip fracture and non-hip fracture subjects. One-hundred and seven women were recruited in the study, 47 women (mean age 81.6 years) with low-energy hip fractures and 60 female non-hip fracture control subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
48
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 58 publications
16
48
2
Order By: Relevance
“…Weight, height, and age results agree well with a previous discriminative study on women,20 confirming that age is a stronger predictor, as well as discriminator, of fracture than either weight or height. However, age shows much more significance for neck fracture than for trochanteric fracture, which may well be related to the particular regions associated with age‐related bone loss23 and how these compare to those regions associated with each fracture type in Fig.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Weight, height, and age results agree well with a previous discriminative study on women,20 confirming that age is a stronger predictor, as well as discriminator, of fracture than either weight or height. However, age shows much more significance for neck fracture than for trochanteric fracture, which may well be related to the particular regions associated with age‐related bone loss23 and how these compare to those regions associated with each fracture type in Fig.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast to QCT, the DXA‐derived areal BMDs contain some measure of size as well as volumetric density, and this may contribute to the improved performance for neck fracture from what is otherwise a less direct measurement of BMD. Nevertheless, hazard ratios between DXA and QCT BMD are largely similar, supporting the general results from previous studies that fail to show any significant benefit from adding such QCT measurement to fracture predictors which already include DXA measurements 19, 20, 29…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…13,14 We analyzed our FE models with 75% of the bone density of the cadaveric bone taken from PhysiomeSpace in accordance with a recent imaging study that showed that the average bone mineral density (BMD) of femoral heads in hip fracture patients was 75% of the BMD of an age-matched fracturefree control group. 15 To calculate the tip-apex distance corresponding to the position of the lag screw, a best-fit sphere was calculated to match the surface nodes of the head. The coordinates of the apex were then obtained by taking into account the neckshaft angle and the femoral neck anteversion of the bone.…”
mentioning
confidence: 99%